Eksistensi Tradisi Hiziban Nahdatul Wathan Pada Masyarakat Barabali, Lombok Tengah, NTB (Equilibrium: Jurnal Pendidikan, 2022)
This research is a qualitative research that discusses the Hiziban tradition as a routine ritual of the community in the village of Barabali, West Nusa Tenggara. Qualitative research is research that produces descriptive data in the form of written or spoken words consisting of observable behaviors. The focus of this research is how the implementation of Hiziban activities in the community in the village of Barabali, what factors influence the continuation of the tradition and how the hiziban tradition affects the religious behavior of the community. From this research it was found that Hiziban Hiziban is a tradition of reading prayers in groups whose prayers are selected prayers compiled by the founder of Nahdlatul Wathan, namely, TGH. Zainuddin Abdul Madjid. Hiziban has become an inherent routine in the Barabali village community. By carrying out the Hiziban tradition, namely, remembrance and prayer, they will reassure their hearts, bring blessings in life and are believed to also benefit everyone who is carrying out hiziban.
Keywords: Hiziban tradition; West Nusa Tenggara community